THE RELATIONSHIP OF MOTHER'S KNOWLEDGE AND PSYCHOLOGICAL CONDITIONS WITH BASIC IMMUNIZATION VISITS IN INFANTS 0-11 MONTHS DURING THE COVID-19 PANDEMIC - Tri Septian Maksum; Nikmatisni Arsad; Widya Cahyaningsih Polontalo (Jambura Journal of Health Sciences and Research, 2022)
The Covid-19 pandemic has had a major impact on community life, one of which is basic immunization activities for infants 0-11 months at the posyandu. In its implementation, there were some worries and anxieties felt by the mothers of posyandu participants who were afraid that their children and themselves were infected by the Covid-19 virus (SARS-CoV-2). Meanwhile, basic immunization is very important for children to prevent various dangerous diseases. This study aims to determine the relationship between mother's knowledge and psychological condition with basic immunization visits for infants 0-11 months during the Covid-19 pandemic. The research location is in the working area of the Ulantha Health Center, Suwawa District, Bone Bolango Regency. This research is included in an analytic observational study with a cross sectional study design. The population is all mothers who have babies aged 0-11 months in the working area of the Ulantha Health Center with a total of 64 people. The number of samples is the same as the total population, namely 64 people obtained using the total sampling technique. Data was collected using a standard Hamilton Anxiety Rating Scale (HARS) questionnaire, and then processed using SPSS. Data were analyzed using chi-square test. The results showed that most of the mothers had good knowledge levels (45.0%), severe psychological conditions (anxiety) (46.9%), and made basic immunization visits during the Covid-19 pandemic (93.8%). There was no relationship between knowledge (p=0.597) and mother's psychological condition (p=0.300) with basic immunization visits for infants 0-11 months during the Covid-19 pandemic. This happens because of the lack of family support and encouragement from health workers and most mothers feel anxious and worried about the current pandemic situation, but they still make immunization visits considering the importance of immunization for children in preventing dangerous diseases. It is recommended for mothers to continue to bring their babies for basic immunization visits even though they are still in the Covid-19 pandemic condition while still implementing strict health protocols.